2021
DOI: 10.1093/jn/nxab021
|View full text |Cite
|
Sign up to set email alerts
|

Local Foods Can Increase Adequacy of Nutrients Other than Iron in Young Urban Egyptian Women: Results from Diet Modeling Analyses

Abstract: Background Nutrition transition and recent changes in lifestyle in Middle Eastern countries have resulted in the double burden of malnutrition. In Egypt, 88% of urban women are overweight or obese and 50% are iron deficient. Their energy, sugar, and sodium intakes are excessive, while intakes of iron, vitamin D, and folate are insufficient. Objective This study aimed to formulate dietary advice based on locally consumed and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Fortification levels of 400 mg of elemental calcium per 100 g of flour were required for young adolescent girls' diets in Barisal to achieve the 100% Ca PRI, while lower levels of 200 or 156 mg/100 g were sufficient for younger children. Other Optifood analyses have concluded that it is harder to reach the Ca PRI of specific nutrients using local foods without the inclusion of fortified flour, rice, and other staple foods or complementary feeding products, specifically for iron among urban Egyptian women 50 ; for zinc and iron among infants and young children (IYC) across Northern Kenya 48 ; for calcium, zinc, and iron for IYC in Indonesia 51 and Cambodia 52 ; and for vitamins B1 and B3, folate, and iron for IYC in Colombia. 53 Fortified water was simulated in the diets of target groups, respectively, of Bangladesh, Guatemala, and Uganda to meet the Ca PRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortification levels of 400 mg of elemental calcium per 100 g of flour were required for young adolescent girls' diets in Barisal to achieve the 100% Ca PRI, while lower levels of 200 or 156 mg/100 g were sufficient for younger children. Other Optifood analyses have concluded that it is harder to reach the Ca PRI of specific nutrients using local foods without the inclusion of fortified flour, rice, and other staple foods or complementary feeding products, specifically for iron among urban Egyptian women 50 ; for zinc and iron among infants and young children (IYC) across Northern Kenya 48 ; for calcium, zinc, and iron for IYC in Indonesia 51 and Cambodia 52 ; and for vitamins B1 and B3, folate, and iron for IYC in Colombia. 53 Fortified water was simulated in the diets of target groups, respectively, of Bangladesh, Guatemala, and Uganda to meet the Ca PRI.…”
Section: Discussionmentioning
confidence: 99%
“…This allows fortified products to be explored as part of whole diets and identify commonly consumed foods that could also be promoted to improve micronutrient intake. 50 However, the modeling in Optifood is a simulation based on overall observed dietary patterns and is unable to explore the percentage of the population at risk of inadequate intake or exceeding the UL of consumption. Other tools, such as the Intake Modeling, Assessment and Planning Program, would be able to provide more refined estimates of risk but would have distinct data requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling realistic diets using LP analysis in Optifood requires data on the current food consumption patterns of a specific population (defined by age, sex, and region), including food types, quantities consumed, and frequency of consumption 13 . Individual 24‐h recall (24HR) data are the most common source used to generate Optifood LP input parameters 1–3,5,14–17 . Unfortunately, the collection of quantitative individual‐level dietary intake data, through 7‐day observed‐weighed food records (the gold standard) or 24HRs, is complex and expensive in terms of time and resources 18–20 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Individual 24-h recall (24HR) data are the most common source used to generate Optifood LP input parameters. [1][2][3]5,[14][15][16][17] Unfortunately, the collection of quantitative individual-level dietary intake data, through 7-day observed-weighed food records (the gold standard) or 24HRs, is complex and expensive in terms of time and resources. [18][19][20] These data constraints often make LP analyses unfeasible, 18,[21][22][23] which severely limits opportunities for evidencebased programmatic decision making using LP.…”
Section: Introductionmentioning
confidence: 99%